Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Melalui Metode Pembelajaran Tanya Jawab (Questions Answer) pada Siswa Kelas VI SDN 26 Sungai Limau - Hayati S.Pd (JURNAL MANAJEMEN PENDIDIKAN, 2016)
Abstract Question and answer method is a way of presenting a lesson in the form of questions to be answered, especially from teachers to students, but can also be from student to teacher. The problems to be examined in this study is: Does the use of learning methods FAQ (Questions and answers) can improve learning outcomes Indonesian students Class VI SDN 26 Sungai Limau? The purpose of this action research is to improve learning outcomes Indonesian through the use of learning methods FAQ (Questions and answers) on a class VI student of SDN 26 Sungai Limau.Penelitian using action research as much as two rounds. Each round consists of four phases: planning, implementation, observation and reflection. Goal of this research is a Class VI student of SDN 26 Sungai Limau. The data obtained are quantitative data and analysis results kualitatif.Dari learning methods FAQ (Questions and answers) had a positive impact in improving student learning outcomes characterized by increased mastery learning students in each cycle, the first cycle (66.67%), the second cycle ( 87.88%). the conclusion of this study is the learning method FAQ (Questions and answers) have a positive effect, which can increase student learning outcomes are indicated with an average response of students stating that the student interested and are interested in learning methods FAQ (Questions and answers ) so that they become motivated to learn.Keywords: Indonesian, Learning Method debriefing